PELATIHAN KONSELING REALITA SEBAGAI UPAYA PENINGKATAN KARAKTER HARDINESS SISWA PADA MGBK SMP SE-KOTA SEMARANG - Mulawarman Mulawarman; Dwi Yuwono Puji Sugiharto; Eni Rindi Antika; Achmad Miftachul ‘Ilmi; Thrisia Febrianti; Nabila Fuadina; Alvia Ainil Lathifah; Ilma Zaerotul Farida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2024)
The role of counselors is important in supporting student development, especially considering the low hardiness character of junior high school students. The counselor's professionalism in providing comprehensive counseling services is decisive in handling students' hardiness character. One of counseling approach which can improve students' hardiness character is reality counseling. Therefore, the community service team conducted reality counseling training as an effort to improve students' hardiness character at MGBK SMP in Semarang City. The method of implementing uses three stages consisting of participant identification, training implementation, and evaluation. The service activities were carried out for two days with 35 participants from junior high school counselors in Semarang City. The first day's activities focused on increasing participants' knowledge with material presentation by the community service team related to the topic of counselor responsive competencies in the VUCA Era, hardiness character and mind-skills, and reality approach counseling. The second day involved simulation and supervised practice, followed by a reflection and evaluation session. The results of the paired samples t-test showed a significant differences between the average pre-test and post-test scores with a value of Sig. 2-tailed=0.000 (<0.01). It means that there is an effect of training implementation on the counselor's ability to use reality counseling. This is supported by, positive evaluation that shows satisfaction of the trainees during the service activities. Trainees can implement reality counseling in their respective schools to improve the hardiness character of junior high school students